Clinical and imaging characteristics of osteitis condensans ilii as compared with axial spondyloarthritis. (23rd May 2020) - Poddubnyy, Denis; Weineck, Henning; Diekhoff, Torsten; Redeker, Imke; Gobejishvili, Nino; Llop, Maria; Rodriguez, Valeria Rios; Proft, Fabian; Protopopov, Mikhail; Haibel, Hildrun; Sieper, Joachim; Hermann, Kay Geert A
Abstract: Objectives: Osteitis condensans ilii (OCI) has become an important differential diagnosis for axial spondyloarthritis (axSpA). The objective of this matched case–control study was to investigate demographic, clinical, laboratory and MRI characteristics of OCI as compared with axial spondyloarthritis (axSpA). Methods: A total of 60 patients diagnosed with OCI were included in the final analysis. From 27 of these patients, MRIs of the sacroiliac joints were available. OCI patients were matched with a 1:1 ratio by back pain duration to patients with definite axSpA in order to compare clinical, laboratory and MRI characteristics. Results: The OCI patients were nearly all females (96.7 vs 46.7%), had a significantly lower prevalence of inflammatory back pain (39.5 vs 88.9%), a significantly lower percentage of HLA-B27 positives (35.2 vs 80.0%) and a lower prevalence of the majority of other SpA features as compared with axSpA patients. Interestingly, there was no difference in the prevalence of osteitis in the sacroiliac joints (92.6 vs 85.2% in OCI and axSpA, respectively, P  = 0.44), but there was a difference in the prevalence of erosions (7.4 vs 66.7%, respectively, P  = 0.0001). In addition, in OCI nearly all lesions were localized in the anterior part of the sacroiliac joints while in axSpA lesions were localized predominantly in the middle part of the joint (for osteitis: 96 vs 4% in OCI and 28.6 vs 71.4% in axSpA; P  = 0.0002 for the inter-group difference). Conclusion: Clinical and imaging features of OCI compared with axSpA are described that should help in differential diagnosis.